Identification of Microbiota Causing Bromhidrosis in the Axillary - Putri Wahdiah Utama; Nelva Karmila Jusuf; Imam Budi Putra; Muhammad Ichwan; R. Lia Kusumawati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Bromhidrosis is a clinical condition defined by an uncomfortable or unpleasant body odor. Since the apocrine glands are only active during puberty, most bromhidrosis occurs in the apocrine glands in the armpit and occurs when apocrine gland secretions approach the skin's surface, where they undergo various biochemical reactions caused by the presence of microbiota in the axillary skin, resulting in odor in the axilla. This research aims to identify microbiota species in the axilla that can cause bromhidrosis. A laboratory experimental research design with purposive sampling is used in this study. In this study, 60 samples were collected from students aged 15 to 18 years old at a high school in Medan, and the samples were analyzed at the University of North Sumatra Hospital's Microbiology Laboratory. All samples were taken from the right axillary skin swab, a Gram stain was performed, and the identified microbiota isolates were identified. The results of skin smear culture revealed a Gram-positive cocci group in 59 samples (98.3%) and a Gram-positive bacilli group in only one sample (1.7%). The microbiota responsible for bromhidrosis was identified as Staphylococcus hominis spp. hominins (30.4%), Staphylococcus epidermidis (27.8%), Staphylococcus aureus (16.5%), Kocuria kristinae and Staphylococcus haemolyticus (6.3%), Staphylococcus lugdunensis and Staphylococcus saprophyticus. The most common microbiota that causes bromhidrosis in the axilla is Staphylococcis hominis spp. Hominis, Staphylococcus epidermidis, and Staphylococcus aureus.